Some legal aspects of satellite television / James Redas Noel - Noel, James Redas (Faculty of Law, 1986)
The International Telecommunication Union Regulations 1refiect the genius of the people to whom they apply. Telecommunication Regulations develop imperceptibly from usage and therefore reflect the aims and the aspirations of the United Nations. Direct STV2 is one example where nations unite themselves through the INTELSAT and share information almost instantaneously. Telecommunication law is a product of these aims and aspirations: to regulate and control the use of Telecoms System through legal means. It has and will continue to play a vital role in STV for promoting ideas through TV3 programmes. How these are achieved and regulated is tile central issue of this paper. Legislation has in many respects, affected the administration of STV transmission, its broadcast and even the establishment of a TV station. The modern technology, has made it possible that others may reap what they did not sow.